Mechanical properties of sustainable concrete due to the use of steel-kenaf fiber - Hammood, Rasheed Abed; Sharifah Maszura, Syed Mohsin (2019)
This paper presents an experimental study on the mechanical properties of the steel-kenaf hybrid fiber concrete mixture. Two types of fibers, steel hooked-end fiber and kenaf fiber were considered. To have reference concretes, a plain mixture without fibers was considered and two mixture containing of steel-kenaf hybrid fiber with 1% and 2% by volume were prepared. Mechanical properties, compressive strength and flexural strength were studied. In this study, kenaf fiber were treated by (NaoH) concentration at 6%, immersion duration at 24 hours under conditions of laboratory temperature. The results showed that improve was observed for all the mixtures with hybrid fiber on the compressive and flexural strengths of steel-kenaf hybrid fiber concrete mixture. Specimens with hybrid fibers show the best flexural performance. Moreover, an increase in volume fractions of steel fibers leads to increase in the compressive and flexural strengths of concrete. In addition, specimens with steel -kenaf hybrid fibers exhibit a better failure behavior than specimens without fibers.